Structure of Recombinant Rabies Virus Nucleoprotein-RNA Complex and Identification of the Phosphoprotein Binding site - Schoehn, Guy (American Society for Microbiology, 2001)
Rabies virus nucleoprotein (N) was produced in insect cells, in which it forms nucleoprotein-RNA (N-RNA) complexes that are biochemically and biophysically indistinguishable from rabies virus N-RNA. We selected recombinant N-RNA complexes that were bound to short insect cellular RNAs which formed small rings containing 9 to 11 N monomers. We also produced recombinant N-RNA rings and viral N-RNA that were treated with trypsin and that had lost the C-terminal quarter of the nucleoprotein. Trypsin-treated N-RNA no longer bound to recombinant rabies virus phosphoprotein (the viral polymerase cofactor), so the presence of the C-terminal part of N is needed for binding of the phosphoprotein. Both intact and trypsin-treated recombinant N-RNA rings were analyzed with cryoelectron microscopy, and three-dimensional models were calculated from single-particle image analysis combined with back projection. Nucleoprotein has a bilobed shape, and each monomer has two sites of interaction with each neighbor. Trypsin treatment cuts off part of one of the lobes without shortening the protein or changing other structural parameters. Using negative-stain electron microscopy, we visualized phosphoprotein bound to the tips of the N-RNA rings, most likely at the site that can be removed by trypsin. Based on the shape of N determined here and on structural parameters derived from electron microscopy on free rabies virus N-RNA and from nucleocapsid in virus, we propose a low-resolution model for rabies virus N-RNA in the virus.